Role of Astrocytes in Epilepsy - Coulter, Douglas A. (Cold Spring Harb Perspect Med, 2015)
Astrocytes express ion channels, transmitter receptors, and transporters and, thus, are endowed with the machinery to sense and respond to neuronal activity. Recent studies have implicated that astrocytes play important roles in physiology, but these cells also emerge as crucial actors in epilepsy. Astrocytes are abundantly coupled through gap junctions allowing them to redistribute elevated K(+) and transmitter concentrations from sites of enhanced neuronal activity. Investigation of specimens from patients with pharmacoresistant temporal lobe epilepsy and epilepsy models revealed alterations in expression, localization, and function of astroglial K(+) and water channels. In addition, malfunction of glutamate transporters and the astrocytic glutamate-converting enzyme, glutamine synthetase, has been observed in epileptic tissue. These findings suggest that dysfunctional astrocytes are crucial players in epilepsy and should be considered as promising targets for new therapeutic strategies.